Relationship between knowledge and attitude about dental health with incidence of dental disease - Dewi Purnama Windasari; Zulkarnaen, Iskandar; N, Nurhaeda; Marisda, Dewi Hikmah (PT.Mantaya Idea Batara, 2022)
Dental and oral health is part of the general welfare of humans that can improve health. Data from the Ministry of Health in 2017 shows that the prevalence of caries in Indonesia reaches 60-80% of the population. The purpose of the study was to determine the relationship between knowledge and attitudes of children about dental health with the incidence of dental disease. This research is a quantitative research with analytic observational research type and cross sectional approach. The sampling technique used is the total sampling technique with a total sample of 81 respondents from class V SD Inpres Tangalla. The results of the study using the Chi Square statistical test showed the value of x2 = 51,100 (x2 > 3841) which means that there is a relationship between children's knowledge of dental health and the incidence of dental disease, the value of x2 = 67,331 (x2 > 3841). The conclusion of this study is that there is a relationship between knowledge and attitudes of children towards dental health and the incidence of dental disease. It is hoped that the fifth grade students of SD Inpres Tangalla will improve their dental health by getting used to a healthy lifestyle